Main Directions of Development of E-Commerce Based on Information Technology - Suleymanov, G.S.; Ismayilova, H.G. (Herald of Azerbaijan Engineering Academy, 2024)
The development of the Internet, as well as the World Wide Web (WWW), reflects the growing interest and importance of e-commerce for businesses and industries. At this time, questions arise about how to manage e-commerce and payment transactions, various security issues, etc. With the advent of the Internet and the World Wide Web (WWW), a new medium has emerged that is more dynamic than radio or television. The number of companies in the world that conduct all their business transactions over the Internet and operate entirely in the e-commerce industry is increasing every day. The work analyzed the main indicators of ICT infrastructure in Azerbaijan, the ICT development index, as well as the current state of e-commerce in the country. The work also puts forward a number of proposals for the development of e-commerce and eliminating shortcomings.